الذكـاء العاطفـي للمعلم ودوره فـي تحقيق التوافق المهني دراسة ميدانية على عينة من معلمي الحلقة الأولى من التعليم الأساسي في مدينة اللاذقية (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث إلى دراسة الذكاء العاطفي للمعلم ودوره في توافقه المهني, وتتلخص مشكلة البحث بالسؤال التالي: ما هي العلاقة بين الذكاء العاطفي والتوافق المهني لمعلمي الحلقة الأولى من التعليم الأساسي؟ بلغ حجم العينــــة 250 معلماً ومعلمة من معلمي الحلقة الأولى من التعليم الأساسي فــــــي مدينة اللاذقية وتم سحب العينة بالطريقة العشوائية من المدارس التالية:صقر قريش , الاشتراكية ,أنيس عباس, قنينص, نادر جراد, فارس صبيح, الشريف الرضي,الفارابي, يوسف فارس, سليم عمران).واستخدم مقياس الذكاء العاطفي لفاروق عثمان و محمد عبد السميع, ومقياس التوافق المهنـــي لــ هيو .م.بل ,إعداد عباس عوض, للحصول علــــــى البيانات مـــــــن أفراد العينــــــة. كما تــــم استخدام مجموعــــــة مـــــــن الأساليب الإحصائيـــــة (معامــــل الارتباط بيرسون,  معامــــل ألفا كرومباخ, واختبار الدلالــــــــة t-testستودنت) وتوصل البحث للنتائج التاليــــة: 1 –لا توجد فروق ذات دلالة إحصائية بين المعلمين والمعلمات في متوسط درجات الذكاء العاطفي. 2- لا توجد فروق ذات دلالة إحصائية بين المعلمين والمعلمات في متوسط درجات التوافق المهني. 3- توجد علاقة ذات دلالة إحصائية بين درجات الذكاء العاطفي للمعلمين والمعلمات ودرجات توافقهم المهني. This research aims to study teacher's emotional intelligence and its role inprofessional adjustment. The research problem was represented in the following main question: what is the relationship between emotional intelligence and professional adjustment of First Grades Teachers in primary schools? The sample of this research was consisted of (250) teachers (male and female)from the teacher of the first Grades in primary schools in Lattakia. They are chosen randomly from the following schools :(Saker Quraish, Al-eshterakia, Anes Abass,Kohnenas, NaderJrad, Fares Sbeikh, Al-shareef Al-Radee, Al-earaby, Yoseef Fares, SaleemOmran). A combination of scale was used in this research including ascale of emotional intelligence of (FarokOthmam and Mohamed Abdul Samea),and a scale of professional adjustment of (Hyou.MBel).Researcher used statistical methods as following:(T test, correlation coefficient person test,Alfa test), the research out com revealed the following: 1-   There are no statistically significant differences  between  teachers  (male and female) in average degrees of emotional intelligence 2-   There is no statistically significant differences between the teachers (male and female) in  average degrees professional adjustment. 3-   There is statistically significant associationbetween average degrees teachers emotional intelligence and average degrees  professional adjustment .